Risks of Cryptocurrency Investment from the Perspective of Sharia Economic Law - Ashilla Nadiya Amany; Francinita Putri; Bima Cinintya Pratama (UM Purwokerto Press, 2022)
Money is a medium of exchange used to pay for goods or services. However, over time, the function of money evolved so that it could be used as a unit of account and a store of value. The development of the digital era provides economic convenience, resulting in a change in the use of money, one of which is the emergence of crypto or cryptocurrency investments that are used as digital currencies. Because there is no official permit from the government or state financial institutions, the existence of cryptocurrency investment in Indonesia is still questionable. So there is a high enough risk to invest there, such as if the investor loses money when the cryptocurrency's price falls. The methodology employed in this study is descriptive, with a qualitative approach. To evaluate the risk of cryptocurrency investment through the lens of Islamic economics.